Reducing Losses and Energy Storage Requirements of Modular Multilevel Converters With Optimal Harmonic Injection - Simon Fuchs; Jurgen Biela (IEEE Access, 2023)
Due to the single phase characteristic of the individual arms of the Modular Multilevel Converter (MMC) topology, the difference between the instantaneous AC and DC side power must be buffered in the module capacitors. This results in large module capacitors compromising the power density and cost of the MMC. In this paper, a multi-objective optimization scheme is formulated that aims at reducing the required module capacitance and the semiconductor losses at the same time. Further attention is paid to the maximum AC voltage amplitude or the maximum current. The optimization scheme is based on the injection of circulating current and AC common mode voltage harmonics. Unlike most existing optimization schemes it considers the actual trajectories of capacitor voltage and arm output voltage to maximize the savings in module capacitance and semiconductor losses. For an exemplary medium voltage MMC parameter set, capacitance value reductions of more than 50% are achieved while the semiconductor losses decrease by 8- 18%. Based on a volume estimation for MMC modules, this results a volume reduction of up to 45%.